PENGARUH KONSENTRASI KARAGENAN DAN PEKTIN TERHADAP KUALITAS GEL PENGHARUM RUANGAN BERBAHAN BAKU MINYAK ATSIRI BATANG SERAI DAPUR - Dewi Suryani; Yudha Irhasyuarna; Rizky Febriyani Putri (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This research is a test of air freshener gel with gel-forming ingredients, namely carrageenan and pectin and adding natural fragrance ingredients, kitchen lemongrass stem essential oil. The research aims to see the quality of carrageenan and pectin concentrations which play a role in the preparation base for air freshener gel, determine the best concentration of kitchen lemongrass stem essential oil for use as room freshener gel and determine the best liquid evaporation rate in air freshener gel under various room conditions. The type of research used was experimental RAL (Completely Randomized Design). Data collection techniques use testing and observation. The results of the research show (1) the quality of the concentration of carrageenan and pectin used for the air freshener gel base is the best ratio, namely at 90:10 with the properties of the gel being elastic, supple, not easily destroyed and having the lowest syneresis; (2) a 4% concentration of lemongrass stem essential oil is the most preferred; (3) essential oil of kitchen lemongrass stems concentration of 4% as an air freshener gel with the greatest evaporation of the liquid in the gel placed in a room with a fan.